2023
DOI: 10.3390/antibiotics12060988
|View full text |Cite
|
Sign up to set email alerts
|

An Edible Biopolymeric Microcapsular Wrapping Integrating Lytic Bacteriophage Particles for Salmonella enterica: Potential for Integration into Poultry Feed

Abstract: This research work aimed at developing an edible biopolymeric microcapsular wrapping (EBMW) integrating lytic bacteriophage particles for Salmonella enterica, with potential application in poultry feed for biocontrol of that pathogen. This pathogen is known as one of the main microorganisms responsible for contamination in the food industry and in foodstuff. The current techniques for decontamination and pathogen control in the food industry can be very expensive, not very selective, and even outdated, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 94 publications
(189 reference statements)
0
5
0
Order By: Relevance
“…The phage particles were centrifuged in a micro-ultracentrifuge from Beckman-Coulter (model Optima TLX, Indianapolis, IN, USA) for 150 min at 45,000 rpm and 4 °C. The samples were negatively stained employing uranyl acetate at 2% ( w / v ) and pH 7.0, [ 21 , 22 ] and photomicrographed in a Transmission Electron Microscope from JEOL (model JEM 2100, Tokyo, Japan) using a high-resolution CCD camera from GATAN Inc. (model ORIUS™ 832.J4850 SC1000B, Pleasanton, CA, USA). The software Gatan Microscopy Suite (DigitalMicrograph from GATAN Inc., version 2.11.1404.0) was used to obtain digital photos of the phage virions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phage particles were centrifuged in a micro-ultracentrifuge from Beckman-Coulter (model Optima TLX, Indianapolis, IN, USA) for 150 min at 45,000 rpm and 4 °C. The samples were negatively stained employing uranyl acetate at 2% ( w / v ) and pH 7.0, [ 21 , 22 ] and photomicrographed in a Transmission Electron Microscope from JEOL (model JEM 2100, Tokyo, Japan) using a high-resolution CCD camera from GATAN Inc. (model ORIUS™ 832.J4850 SC1000B, Pleasanton, CA, USA). The software Gatan Microscopy Suite (DigitalMicrograph from GATAN Inc., version 2.11.1404.0) was used to obtain digital photos of the phage virions.…”
Section: Methodsmentioning
confidence: 99%
“…The appropriate phage virion/bacterial cell ratio (i.e., Multiplicity Of Infection—MOI), aiming at the inactivation of host bacteria (viz. MOI 100 and MOI 1000), was used based on a previous work by Pereira et al [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Pereira et al.’s study, they developed an edible biopolymer microcapsule packaging for intestinal Salmonella, integrating lytic bacteriophage particles. For the formulation, a concentration of 2% (w/w) sodium alginate was added ( 130 ). To enhance colorectal cancer (CRC) chemotherapy effectiveness, nucleic acid bacteriophage-specific bacteriophages were conjugated with glucan nanoparticles loaded with CRC chemotherapeutic drugs to form bacteriophage-guided nanoparticles, which effectively inhibited nucleic acid bacteriophage growth and significantly extended the survival time of CRC mice ( 131 ).…”
Section: Optimizing Formulation and Encapsulation Strategies For Phag...mentioning
confidence: 99%
“…Furthermore, Soto et al [ 149 ] observed that phages encapsulated in a calcium alginate matrix had their presence extended for an extra 100 h in a water flow system, which simulated the automatic birdbaths used in the poultry industry, when compared to non-encapsulated phages. In another research work [ 23 ], the development of calcium alginate microparticles involving a mixture of gelatin, calcium chloride and chitosan, to encapsulate a cocktail of two lytic phages against Salmonella enterica has been reported, aiming at the oral treatment of Salmonellosis in chickens. Table 6 shows different experiments using encapsulated phages for animal treatments.…”
Section: Phage Delivery Strategies For Animal Health and Food Applica...mentioning
confidence: 99%
“…There is much research examining the efficacy of using phages as antibacterials, specifically in food-animal production, aiming to control bacterial diseases [ 22 ]. Particularly, phages have been studied for controlling bacterial diseases in poultry [ 7 , 11 , 23 , 24 ], pigs [ 22 ], calves [ 25 ], and fish [ 26 ]. Zoonotic pathogens associated with poultry and pigs, such as Salmonella spp., E .…”
Section: Introductionmentioning
confidence: 99%